Analisis Penerapan Sanitation Standard Operating Procedure (SSOP) dalam Produksi Permen Jelly Lidah Buaya - Yuniasih, Annisa Wirrdiana (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
In order to maintain food safety, it is necessary to optimize the implementation of Sanitation Standard Operating Procedure (SSOP) in the food industry of a processed product. Guaranteed food security can meet quality and sustainable food security. The purpose of this study is to analyze and evaluate the application of SSOP in MSMEs